Persistence and stochasticity are key determinants of genetic diversity in plants associated with banded iron formation inselbergs - Byrne, M.; Krauss, S.; Millar, M.; Elliott, C.; Coates, D.; Yates, C.; Binks, R.; Nevill, Paul; Nistelberger, H.; Wardell-Johnson, Grant; Robinson, Todd; Butcher, R.; et al. (Wiley-Blackwell Publishing Ltd., 2018)
The high species endemism characteristic of many of the world's terrestrial island systems provides a model for studying evolutionary patterns and processes, yet there has been no synthesis of studies to provide a systematic evaluation of terrestrial island systems in this context. The banded iron formations (BIFs) of south-western Australia are ancient terrestrial island formations occurring within a mosaic of alluvial clay soils, sandplains and occasional granite outcropping, across an old, gently undulating, highly weathered, plateau. Notably, these BIFs display exceptionally high beta plant diversity. Here, we address the determinants and consequences of genetic diversity for BIF-associated plant species through a comprehensive review of all studies on species distribution modelling, phylogenetics, phylogeography, population genetics, life-history traits and ecology. The taxa studied are predominantly narrowly endemic to individual or a few BIF ranges, but some have more regional distributions occurring both on and off BIFs. We compared genetic data for these BIF-endemic species to other localised species globally to assess whether the unique history and ancestry of BIF landscapes has driven distinct genetic responses in plants restricted to this habitat. We also assessed the influence of life-history parameters on patterns of genetic diversity. We found that BIF-endemic species display similar patterns of genetic diversity and structure to other species with localised distributions. Despite often highly restricted distributions, large effective population size or clonal reproduction appears to provide these BIF-endemic species with ecological and evolutionary resilience to environmental stochasticity. We conclude that persistence and stochasticity are key determinants of genetic diversity and its spatial structure within BIF-associated plant species, and that these are key evolutionary processes that should be considered in understanding the biogeography of inselbergs worldwide.